Regulation of NK Cell Activation and Effector Functions by the IL-12 Family of Cytokines: The Case of IL-27 - Zwirner, Norberto Walter; Ziblat, Andrea (Frontiers in Immunology, 2017)
Natural killer (NK) cells are characterized by their ability to detect and induce apoptosis of susceptible target cells and by the secretion of immunoregulatory cytokines such as IFN-gamma. The activation of these effector functions is triggered upon recognition of tumor and pathogen (mostly virus)-infected cells and as a consequence of a bidirectional crosstalk that NK cells establish with other cells of myeloid origin such as dendritic cells (DC) and macrophages. A common characteristic of these myeloid cells is their ability to secrete different members of the IL-12 family of cytokines such as IL-12, IL-23 and IL-27, and cytokines such as IL-15 and IL-18. Although the effect of IL-12, IL-15 and IL-18 has been characterized, the effect of IL-23 and IL-27 on NK cells (especially human), remains ill-defined. Particularly, IL-27 is a cytokine with dual functions as it has been described as pro- and as anti-inflammatory in different experimental settings. However, recent evidence indicates that this cytokine indeed promotes human NK cell activation, IFN- secretion, NKp46-dependent NK cell-mediated cytotoxicity and antibody (Ab)-dependent NK cell-mediated cytotoxicity (ADCC) against monoclonal Ab (mAb)-coated tumor cells. Remarkably, IL-27 also primes NK cells for IL-18 responsiveness, enhancing these functional responses. Consequently, IL-27 acts as a pro-inflammatory cytokine that, in concert with other DC-derived cytokines, hierarchically contributes to NK cells activation and effector functions, which likely contributes to foster the adaptive immune response in different physiopathological conditions.